Discovery of novel triazolophthalazine derivatives as DNA intercalators and topoisomerase II inhibitors. Issue 6 (8th February 2021) - Sakr, Helmy; Ayyad, Rezk R.; El‐Helby, Ali A.; Khalifa, Mohamed M.; Mahdy, Hazem A.
Abstract: A new series of triazolophthalazine derivatives was designed and synthesized as topoisomerase II (Topo II) inhibitors and DNA intercalators. The synthesized derivatives were evaluated in vitro for their cytotoxic activities against three human cancer cell lines: HepG2, MCF‐7, and HCT‐116 cells. Compound IX b was the most potent counterpart with IC50 values of 5.39 ± 0.4, 3.81 ± 0.2, and 4.38 ± 0.3 µM, as it was about 1.47, 1.77, and 1.19 times more active than doxorubicin (IC50  = 7.94 ± 0.6, 6.75 ± 0.4, and 5.23 ± 0.3 µM) against HepG2, MCF‐7, and HCT‐116 cells, respectively. Additionally, the binding affinity of the synthesized compounds toward the DNA molecule was assessed using the DNA/methyl green assay. Compound IX b showed an excellent DNA binding affinity with an IC50 value of 27.16 ± 1.2 µM, which was better than that of the reference drug doxorubicin (IC50  = 31.02 ± 1.80 µM). Moreover, compound IX b was the most potent member among the tested compounds when investigated for their Topo II inhibitory activity. Furthermore, compound IX b induced apoptosis in HepG2 cells and arrested the cell cycle at the G2/M phase. Additionally, compound IX b showed Topo II poisoning effects at 2.5 μM and Topo II catalytic inhibitory effects at 5 and 10 μM. Finally, molecular docking studies were carried out against the DNA–Topo II complex and DNA, to investigate the binding patterns of the designed compounds. Abstract : A new series of triazolophthalazine derivatives was designed, synthesized, and tested for their activity as topoisomerase (Topo) II inhibitors and DNA intercalators. Compound IX b showed excellent DNA binding affinity, better than doxorubicin, and had the most potent Topo II inhibitory activity. It induced apoptosis in HepG2 cells and arrested the cell cycle at the G2/M phase.